Winding of the DNA helix by divalent metal ions. - Xu, Y C (1997)
When supercoiled pBR322 DNA was relaxed at 0 or 22 degrees C by topoisomerase I in the presence of the divalent cations Ca2+, Mn2+ or Co2+, the resulting distributions of topoisomers observed at 22 degrees C had positive supercoils, up to an average delta Lk value of +8.6 (for Ca2+at 0 degrees C), corresponding to an overwinding of the helix by 0.7 degrees/bp. An increase of the divalent cation concentration in the reaction mixture above 50 mM completely reversed the effect. When such ions were present in agarose electrophoresis gels, they caused a relaxation of positively supercoiled DNA molecules, and thus allowed a separation of strongly positively supercoiled topoisomers. The effect of divalent cations on DNA adds a useful tool for the study of DNA topoisomers, for the generation as well as separation of positively supercoiled DNA molecules.